A Critical Review on Dooshivishari Agada: A Herbo Mineral Formulation (International Journal of Ayurveda and Pharma Research, 2022)
Dooshivisha (cumulative toxicity) is a type of Kritrima visha (artificial poison). It is a transformed state of other types of poison if not eliminated, get collected in small doses leads to this type of poisoning. It is a unique concept of Ayurveda and is the cause of the majority of the health issues in the present era. Acharyas have said different treatment principles for the management of Dooshivisha (cumulative toxicity). Dooshivishari agada is the formulation of choice for its treatment, which is a herbo-mineral formulation comprised of twelve ingredients that are taken in equal amounts for the preparation. Many Acharyas such as Sushruta, Vagbhata, and Bhavaprakasha have explained it in their classical texts. Along with Dooshivisha (cumulative toxicity), it can also be used in its complications, and also for the treatment of all types of poisoning and other associated signs and symptoms.